Making Sense of the Problem: Stories of Experience and Narrative Inquiry of COVID-19 Students - Dhakal, Bhakta Prasad (DMC Journal, 2024)
This qualitative study aimed to understand students' experiences during the COVID-19 pandemic through semi-structured interviews. The study involved 102 key informants for a research paper and they were the students studying management at TU. Storytelling by the participants is a powerful tool for understanding life experiences and promoting discussion on current issues. Inquiry is increasingly used in educational research as human beings are telling their experiences to talk about particular times and events. Data revealed negative impacts on personal life, learning, working life, and social-emotional experiences. The study suggests that educational stakeholders should focus on students’ voices to engage, motivate, and support students' personal, working, educational, social, and emotional well-being. The emphasis should be given to the importance of student voice in their lives. For this, the storytelling method was used, which is a powerful tool for understanding life experiences and promoting discussion on current issues. This project used narrating inquiry to gather information about the COVID-19 experiences of the students and it used content analysis methodology to analyze responses from students' narrative inquiry interviews, revealing their positive and negative experiences.